Dimensional and structural stability of gamma irradiated stacked die quad flat no leads (QFN) - Siew, Peng Foo; Wan Yusmawati Wan Tusoff,; Azman Jalar, (Universiti Kebangsaan Malaysia, 2014)
The physical properties and structural stability of the Quad Flat No-Leads (QFN) package with different gamma radiation doses have been investigated. The packages were irradiated with Co-60 gamma radiation with varying doses of 5 Gy, 50 Gy, 500 Gy, 5 kGy and 50 kGy with operating dose of 2.54 kGy/h at room temperature. The infinite focus microscope (IFM) was used to measure the dimensional change and slanting/warpage behaviour, while the 3D CT Scan X-ray machine was used to determine the occurrence of deflection on a wire in package due to exposure. It is believed that radiation effect on ceramic filler in the epoxy mold compound (EMC) plays an important role to induce the defects and resulted in swelling of the package. The slanting/warpage behaviour is believed to be caused by the swelling behaviour of ceramic filler and further induced structural stability. The induced stress on the EMC structural after the dimensional change and slanting/warpage failure leads to the occurrence of wire sweep. The finding suggests that defect production in swelled ceramic filler leads to the occurrence of dimensional and structure instability.